Opportunities and barriers to sustainability innovation adoption in a UK water and sewerage company - Tanner, Aaron. (Cranfield University, 2011)
Over the last twenty years, the concepts of sustainability and sustainable development have assumed political importance around the world, and have been largely embraced by governments and prominent international institutions. These concepts have been a means of tackling the challenges of population growth and environmental change. For the UK water sector, these concepts now represent a multitude of challenges. The confluence of climate change and population growth is reducing access to, and the availability of, water resources. The financial costs of inputs such as energy, chemicals, materials and cost of process by-products such as greenhouse gases, carbon, and waste services continue to rise. Government regulators are demanding an improvement in the quality of services, increasingly stringent conditions for emissions to water, air or land, catchment-specific management of the water environment, and the adoption of longterm planning horizons. The UK government has expectations that the water sector will play a role in the delivery of its targets for reducing energy consumption and carbon emissions. Society demands that WaSCs engage in high-level stakeholder consultations and employ long-term visions to guide their decision-making. Finally, WaSCs are increasingly expected to demonstrate and respond to local and global concerns (under the rubric of corporate responsibility) to further justify their value to society. Cont/d.
Keywords: innovation; sustainability; asset-management; Indicators; decision-making; wastewater systems; barriers; opportunities; influence; adoption; water utilities; asset delivery